2022
DOI: 10.3390/foods11131821
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Hypoglycemic Activity of a Novel Pumpkin Peel Polysaccharide-Chromium(III) Complex

Abstract: The aim of our study was to synthesize a pumpkin peel polysaccharide (PPP)-Cr(III) complex and investigate its hypoglycemic activity. Firstly, a novel PPP-Cr(III) complex with a Cr content of 23.77 mg/g was synthesized and characterized. Physicochemical characterization indicated that PPP-Cr(III) had some changes in chemical composition, monosaccharide composition, and morphological structure compared with PPP. The molecular weights of PPP-Cr(III) and PPP were 1.398 × 106 g/mol and 3.386 × 106 g/mol, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Metal ions incorporated with polysaccharides are a good strategy to obtain the complex with stronger biological activities. The pumpkin peel polysaccharide (PPP)‐Cr (III) complex was prepared to enhance the hypoglycemic activity of PPP alone (Zhang et al., 2022). Results showed that PPP‐Cr (III) had better hypoglycemic activity to inhibit α‐glucosidase and insulin resistance through the AMPK/GSK‐3β signaling pathway.…”
Section: Resources Structures and Functional Properties Of Pnpsmentioning
confidence: 99%
“…Metal ions incorporated with polysaccharides are a good strategy to obtain the complex with stronger biological activities. The pumpkin peel polysaccharide (PPP)‐Cr (III) complex was prepared to enhance the hypoglycemic activity of PPP alone (Zhang et al., 2022). Results showed that PPP‐Cr (III) had better hypoglycemic activity to inhibit α‐glucosidase and insulin resistance through the AMPK/GSK‐3β signaling pathway.…”
Section: Resources Structures and Functional Properties Of Pnpsmentioning
confidence: 99%
“…Polysaccharides are natural biomacromolecules consisting of more than ten monosaccharide units linked by glycosidic bonds 1 and exhibit a wide range of biological activities, such as immune-modulating, 2 antioxidant, 3 hypoglycemic, 4 and antiinflammatory. 5 Furthermore, polysaccharides play an important role in intestinal health by maintaining the balance of intestinal microbiota and producing beneficial metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are natural biomacromolecules consisting of more than ten monosaccharide units linked by glycosidic bonds and exhibit a wide range of biological activities, such as immune-modulating, antioxidant, hypoglycemic, and anti-inflammatory . Furthermore, polysaccharides play an important role in intestinal health by maintaining the balance of intestinal microbiota and producing beneficial metabolites. , In recent years, several herb and mushroom polysaccharides (e.g., polysaccharides from Lentinula edodes, Ganodorma lucidum, and Astragalus membranaceus) have been successfully applied in functional foods and drugs as the main or auxiliary ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…These exposed sites also provide a basis for chemical modifications [ 8 ]. The chemical modification of polysaccharides by changing the structure or adding new groups can boost the existing bioactivities or bring new functional properties [ 9 , 10 ]. Therefore, it is a potential method to enhance the anti-inflammatory activity of polysaccharides by chemical modifications.…”
Section: Introductionmentioning
confidence: 99%